Aflatoxin contamination in dairy feed during wet and dry seasons in selected rural areas of Sidama zone in Southern Ethiopia - Wubshet Tefera; Gerd Elisabeth Vegarud; Mestawet Taye; Tolosa Taye (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
This study was conducted in the southern region of Ethiopia. The objectives were to assess the occurrence and level of aflatoxin B1 contamination in dairy cow feeds. The analytical technique used was Enzyme-linked immunosorbent assay(ELISA). Two-way ANOVA was used to analyze +the season and location interaction effect. Laboratory analysis showed that 81.2% of the feed samples had a detectable level of AFB1 within the range of 0.067-29.69 µg/kg and with an average of 7.91±5.83 µg/kg. From the positive samples, 52.5 and 4.58% of the feed sample were above EU (5 µg/kg) and USA (20 µg/kg) limits for dairy cattle feed respectively. Average AFB1 concentration during the dry season (8.74± 5.6 µg/kg) is significantly higher (P<0.05) than wet season (7.02± 5.86 µg/kg). This result implies that sustainable good practices should be maintained for all feed harvesting, storage, and feeding practices by feed producers and dairy farmers regarding aflatoxin contamination.